Cash Transfers: the right answer for the poor in developing countries? Visiting Indonesia’s contemporary case study - C. Audori Fathin (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2019)
One of the most popular poverty reduction programs is Cash Transfers (CT). Even though the implementation of CT programs in Indonesia is also useful in providing basic needs for needy families, however, thus, programs are not conveyed a significant effect on poverty reduction. CTs give cash to poor households in order to help them fulfill their basic needs and emphasize the investment of human capital for their children. This study attempts to map out what factors that cause the ineffectiveness of CT programs in Indonesia compare with the success of CT programs in other countries. This study found that Several factors drive the implementation of social protection, particularly cash transfer, in Indonesia is not as successful as what has been being implemented in other countries. Comparing to Europe, Indonesia still lacks resources to support the implementation of CT programs. European countries, despite its advantages on EU integration, already have established infrastructures and human resources.